Realm of blank space: from Chinese brush painting to music appreciation - Jiawei Xu; Yuhang Zhang (Trans/Form/Ação)
This article aims to break down the existing barriers of art classification, adopt interdisciplinary and comparative research methods, draw on the core concepts of “Dao follows nature” of Taoism, “Doctrine of the Mean” of Confucianism and “pure nature of the heart” of Zen, explain the deep meaning of blank space in ink painting, and reveal the cultural background and aesthetic value of silence in music, emphasizing the dialectical relationship between existence and nonexistence, sound and silence in artistic creation. The results indicate that the “silence” in music and the blank spaces in ink paintings have important aesthetic value. In music appreciation, it is important to slow down the pace, pay attention to intervals and interruptions, actively appreciate the art of blank space, and learn to grasp the overall work and appreciate blank space. Through interdisciplinary exploration, this article provides a new path for the understanding and application of music appreciation, thereby promoting philosophical thinking on the deep meaning of music.